Anal gland adenocarcinoma in situ with pagetoid spread: a case report - Kohei Ishioka; Fumikazu Koyama; Hiroyuki Kuge; Takashi Inoue; Shinsaku Obara; Takayuki Nakamoto; Yoshiyuki Sasaki; Yasuyuki Nakamura; Maiko Takeda; Chiho Ohbayashi; Masamitsu Kuwahara; Masayuki Sho (Surgical Case Reports)
Abstract Background Anal gland carcinoma with perianal Paget’s disease is rare, and anal gland carcinoma in situ is extremely rare. No cases of anal gland carcinoma in situ with pagetoid spread have been previously reported. Case presentation Physical examination in a 75-year-old woman revealed an erythematous, inflamed, perianal skin lesion. Neither colposcopy, cystoscopy, colonoscopy, computed tomography, nor magnetic resonance imaging showed evidence of malignant genitourinary or gastrointestinal lesions. Histopathological examination of a biopsy specimen showed many Paget’s cells in the perianal skin lesion and no malignant cells in the rectal or vaginal mucosa. Therefore, primary extramammary Paget’s disease of the anogenital region was suspected, and we performed anus-preserving wide local excision. However, immunohistochemistry revealed a diagnosis of secondary extramammary Paget’s disease due to adenocarcinoma arising from the anal gland. We therefore proceeded with a radical operation. Histopathological examination showed no residual cancer cells. The final diagnosis was anal gland adenocarcinoma in situ with pagetoid spread in the perianal skin. Conclusions This is the first case report of anal gland adenocarcinoma in situ with pagetoid spread. We recommend immunohistochemical analysis of biopsy and locally resected specimens to obtain an accurate diagnosis and determine the appropriate treatment when there is no visible tumor.